New Perspectives in Information Systems and Technologies, Volume 2 - Rocha, Álvaro.; Rocha, Álvaro.; Correia, Ana Maria.; Correia, Ana Maria.; Tan, Felix . B.; Tan, Felix . B.; Stroetmann, Karl . A.; Stroetmann, Karl . A. (Advances in Intelligent Systems and Computing,, 2014)
This book contains a selection of articles from The 2014 World Conference on Information Systems and Technologies (WorldCIST'14), held between the 15th and 18th of April in Funchal, Madeira, Portugal, a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges of modern Information Systems and Technologies research, technological development and applications. The main topics covered are: Information and Knowledge Management; Organizational Models and Information Systems; Intelligent and Decision Support Systems; Software Systems, Architectures, Applications and Tools; Computer Networks, Mobility and Pervasive Systems; Radar Technologies; Human-Computer Interaction; Health Informatics; and Information Technologies in Education.